إجراءات الطلاق في المحاكم الشرعية والعرفية في جنوب غرب نيجيريا : مقارنة بالشريعة الإسلامية - سعد، مرتضى (Ahmad Ibrahim Kulliyyah of Law, International Islamic University Malaysia, 2015)
This thesis compares procedures of divorce in Shariah and Customary Courts in Southwest Nigeria a Comparison with shariah. The family is the basic building block in the construction of any society and it derives its strength and power from marriage. Divorce cases are rampant in Nigeria, particularly in the Southwest, due to non-adherence to divine guidelines on marriage and divorce. The provisions of Islamic law on divorce cannot be misconstrued as license to deny the Quranic and Sunnah approach to life. Women were created as partners in love and harmony, affection and compassion, to live with their husbands as couples. This study finds that divorce is rampant in Southwest Nigeria due to poverty, moral decadence, domestic violence, polygamy and ignorance, etc. These lead to tension and acrimony between the families of the couple and their relatives. The research focuses on restrictions on the will of the spouses in divorce, according to the Islamic law, Quran and Sunnah. It examines the concept of legal divorce and whether judicial procedures are followed in the Customary Courts in Southwest Nigeria. The study analyses various divorce suits and procedures up to the final dissolution of the marriage. It relies on inductive and descriptive approaches and theoretical extrapolation of articles on the subject of research; analytical approach, which focuses on the issues; and doctrinal views. It also explores random interviews conducted with staff of Shariah and Customary Courts in Southwest Nigeria. The comparative section compares divorce proceedings in Shariah and Customary Courts with the provisions of the Islamic Shariah. It also observed proceedings of the Shariah and Customary courts, the supreme and local communities in the states selected for the research. The researcher found out that the Customary Courts are accredited by Nigerian government. The customary courts have rights to adjudicate certain disputes and issues that occur in the Nigerian society, under certain regulations. The Shariah and Customary Courts system are significant in Nigeria since the ancient times, because most of the population of the Country practice Islam.